2022
DOI: 10.1162/jocn_a_01904
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Region- and Network-level Contributions to Episodic Recollection Using Multilevel Structural Equation Modeling

Abstract: The brain is composed of networks of interacting brain regions that support higher-order cognition. Among these, a core network of regions has been associated with recollection and other forms of episodic construction. Past research has focused largely on the roles of individual brain regions in recollection or on their mutual engagement as part of an integrated network. However, the relationship between these region- and network-level contributions remains poorly understood. Here, we applied multilevel struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…DMN-A regions included the bilateral posterior cingulate cortex, the bilateral precuneus, the bilateral medial prefrontal cortex, the bilateral anterior angular gyrus, and a bilateral section of the dorsal prefrontal cortex (see Figure 1a, yellow regions). We focused on regions in the DMN-C and DMN-A networks due to their roles in episodic memory and simulation (Buckner & DiNicola, 2019; Ritchey & Cooper, 2020) and their correspondence with ventral and dorsal subnetworks we have previously identified (Cooper et al, 2021; Kurkela et al, 2022). We note that these were inadvertently mislabeled in our pre-registration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMN-A regions included the bilateral posterior cingulate cortex, the bilateral precuneus, the bilateral medial prefrontal cortex, the bilateral anterior angular gyrus, and a bilateral section of the dorsal prefrontal cortex (see Figure 1a, yellow regions). We focused on regions in the DMN-C and DMN-A networks due to their roles in episodic memory and simulation (Buckner & DiNicola, 2019; Ritchey & Cooper, 2020) and their correspondence with ventral and dorsal subnetworks we have previously identified (Cooper et al, 2021; Kurkela et al, 2022). We note that these were inadvertently mislabeled in our pre-registration.…”
Section: Methodsmentioning
confidence: 99%
“…The DMN-C subnetwork is commonly co-activated with an adjacent, more dorsal DMN subnetwork, labeled DMN-A, which consists of medial frontal and parietal regions. Recent work has shown that these two subnetworks are dissociable in terms of their functional connectivity during event perception (Cooper et al, 2021) as well as their contributions to memory retrieval (Kurkela et al, 2022). In the latter study, when activity estimates from both ventral and dorsal DMN regions were included in a model predicting retrieval success, only the ventral regions significantly predicted success in retrieving event-specific associations.…”
Section: Introductionmentioning
confidence: 99%
“…There are many benefits of creating a latent variable to measure brain function, including improvements in reliability (Cooper et al, 2019;Kim-Spoon et al, 2021), though this approach may sacrifice specificity that comes with testing individual ROIs in separate models. Latent variable approaches have been used to model brain structure and function in prior work (e.g., Baskin-Sommers et al, 2016;Bolt et al, 2018;Kim-Spoon et al, 2021;Kurkela et al, 2022;Lahey et al, 2012). At baseline and PATHWAYS TO ADOLESCENT SOCIAL ANXIETY 10 two years later (Wave 2), social anxiety symptoms were assessed by clinical interviewers and youth self-reported on their symptoms of generalized anxiety and depression.…”
Section: Pathways To Adolescent Social Anxietymentioning
confidence: 99%
“…Our primary analytic approach was to apply factor analysis to identify potential latent factors associated with social reward neural function. Latent variable approaches have been used to model brain structure and function in prior work (e.g., Baskin-Sommers et al, 2016;Bolt et al, 2018;Kim-Spoon et al, 2021;Kurkela et al, 2022;Lahey et al, 2012). There are many benefits of creating a latent factor to measure brain function, including improvements in reliability (Cooper et al, 2019;Kim-Spoon et al, 2021), though this approach may sacrifice specificity that comes with testing individual ROIs in separate models.…”
mentioning
confidence: 99%